Genetic diversity of maize landraces from Tanzania as compared with commercial improved varieties and elite lines through morphological characterization - Kabululu, Mujuni, Sospeter; Feyissa, Tileye; Ndakidemi, Patrick, Alois (My University, 2022)
Maize production challenges require well-known genetic diversity to ensure effective improvement. The study aimed at conducting a morphological evaluation on 50 maize landraces from Tanzania compared with 7 commercial varieties and 11 elite lines from CIMMYT, Kenya. The experiments were conducted in randomized complete block design at three locations in the Arusha region, Tanzania. Data were collected on 19 quantitative and 12 qualitative traits that were subjected to analysis of variance, descriptive and multivariate statistics. Significant variations (p<0.05) were observed for all traits while higher contribution for accessions variability was found with yield, a thousand kernel weight, flowering traits, kernel, ear, and vegetative plant characteristics. Commercial varieties were characterized by significant yield (107.4g per plant) and yield-related parameters of (a thousand seed weight, number of rows per ear, ear diameter, ear length) also early days to tasseling and silking of 67.7 and 73 respectively. CIMMYT elite lines were characterized by significant low plant and ear height of 138.9cm and 50.6cm respectively as well as flint kernel type. Landraces were more diverse in every trait evaluated with a significant long anthesis-silking interval of 7.5 days and a large ear height of 95.9cm. Some landraces (eg TZA 2793 and TZA 5170) expressed significant traits that would be tapped for further crop improvement. Other landraces clustered themselves irregularly in terms of their collection sites within their major group due to the selection and exchange of seeds. Thus, farmers as custodians of landraces are supposed to be involved in systematic selection and breeding.
Keywords: Genetic diversity; ijb; Improved varieties; Landraces; Maize; Morphological characterization